Multilevel governance in farmers’ markets: a stakeholder analysis in Tuscany - Belletti, Giovanni; Torres Salcido, Gerardo; Scarpellini, Paola; Mengoni, Matteo; Marescotti, Andrea (Frontiers in Sustainable Food Systems, 2024)
Farmers’ Markets (FMs) have gained relevance in recent years as increasingly acknowledged to be critical to turn to more equitable food systems, easing agroecological transition, and preserving biocultural heritage. However, the issue of the forms of social and institutional coordination needed to create, organize, manage and promote FMs is a recent topic in the literature, and their governance is still poorly considered. Based on a set of case studies in Tuscany, Italy, this paper intends to contribute to filling this gap by analysing the forms of governance and the role of different stakeholders. The hypothesis is that FMs are social constructions that respond to processes of social and institutional innovation through direct exchanges between producers, consumers and other stakeholders, articulated at both local and non-local level. The aim of the paper is to explore the interactions between stakeholders and the corresponding forms of multi-level governance that emerge. The method for testing the hypotheses is qualitative, through semi-structured interviews to FMs managers and conversations with producers and other stakeholders, conducted between May and August 2022 in Tuscany. The research was complemented by consultation of indirect sources, such as FMs websites and social networks. The results are summarized in the elaboration of a three-dimensional and territorially embedded governance model. The first dimension refers to the management of internal relations between stakeholders within the FM. The second corresponds to the activation of dialogue, negotiation, and agreement with the municipality and other local authorities, and with local farmers’ unions. The third type corresponds to vertical flows between the FMs and extraterritorial bodies, i.e., regional government, regional and national farmers’ unions and other stakeholder associations. It is important to note that at FMs level, processes of hybridization between the different types of governance are established. The article contributes to the analysis of FMs as economic and social constructions and may be useful for establishing comparative frameworks around institutional and collective action dimensions, multi-actor and multilevel studies of governance.